2009
DOI: 10.5194/angeo-27-31-2009
|View full text |Cite
|
Sign up to set email alerts
|

The influence of solar wind on extratropical cyclones – Part 2: A link mediated by auroral atmospheric gravity waves?

Abstract: Abstract. Cases of mesoscale cloud bands in extratropical cyclones are observed a few hours after atmospheric gravity waves (AGWs) are launched from the auroral ionosphere. It is suggested that the solar-wind-generated auroral AGWs contribute to processes that release instabilities and initiate slantwise convection thus leading to cloud bands and growth of extratropical cyclones. Also, if the AGWs are ducted to low latitudes, they could influence the development of tropical cyclones. The gravity-wave-induced v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 91 publications
(135 reference statements)
5
28
0
Order By: Relevance
“…Auroral AGWs may release instabilities that lead to tropospheric convection, convective clouds and storminess (Prikryl et al, 2009). Using the International Satellite Cloud Climatology Project (ISCCP) D1 dataset, a statistically significant response of high-level cloudiness to fast solar wind from coronal holes is found (Prikryl et al, 2003(Prikryl et al, , 2006(Prikryl et al, , 2009. These results are consistent with the previous finding of solar wind influence on mid-latitude tropospheric circulation (Wilcox et al, 1973;Lundstedt, 1984).…”
Section: ) Interplanetary Interaction Regionssupporting
confidence: 71%
See 3 more Smart Citations
“…Auroral AGWs may release instabilities that lead to tropospheric convection, convective clouds and storminess (Prikryl et al, 2009). Using the International Satellite Cloud Climatology Project (ISCCP) D1 dataset, a statistically significant response of high-level cloudiness to fast solar wind from coronal holes is found (Prikryl et al, 2003(Prikryl et al, , 2006(Prikryl et al, , 2009. These results are consistent with the previous finding of solar wind influence on mid-latitude tropospheric circulation (Wilcox et al, 1973;Lundstedt, 1984).…”
Section: ) Interplanetary Interaction Regionssupporting
confidence: 71%
“…Prikryl et al (2001Prikryl et al ( , 2003 have suggested that auroral atmospheric gravity waves (AGWs) are another candidate for the "missing link" between the solar wind and tropospheric weather. Auroral AGWs may release instabilities that lead to tropospheric convection, convective clouds and storminess (Prikryl et al, 2009). Using the International Satellite Cloud Climatology Project (ISCCP) D1 dataset, a statistically significant response of high-level cloudiness to fast solar wind from coronal holes is found (Prikryl et al, 2003(Prikryl et al, , 2006(Prikryl et al, , 2009.…”
Section: ) Interplanetary Interaction Regionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that nowadays there are researches in which the existence of the inverse connection is discussed, i. e. when the AGWs starting their spread from auroral ionosphere regions have an inuence onto extratropical cyclones [28]. Rees et al [30] identied sources at high latitudes of strong vertical winds of more than 100 m/s, resulting from local geomagnetic energy input and subsequent generation of thermospheric gravity waves.…”
mentioning
confidence: 99%